1997
DOI: 10.1111/j.1442-2042.1997.tb00216.x
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Telomerase Activity in Bladder and Prostate Cancer Cell Lines

Abstract: The presence of telomerase may be a biological character of bladder and prostate cancers as well as other malignancies, although it does not always compensate telomere shortening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…A series of our prior studies showed short telomeres of LNCaP and DU145 cells and long telomeres of TSU-Pr1 cells [11,12]. LNCaP and DU145 cells each have a specific telomere length, which is stable regardless of cell division [14]. These findings suggest that a regulatory mechanism exists for limiting telomere elongation by high telomerase activity.…”
Section: Discussionmentioning
confidence: 77%
“…A series of our prior studies showed short telomeres of LNCaP and DU145 cells and long telomeres of TSU-Pr1 cells [11,12]. LNCaP and DU145 cells each have a specific telomere length, which is stable regardless of cell division [14]. These findings suggest that a regulatory mechanism exists for limiting telomere elongation by high telomerase activity.…”
Section: Discussionmentioning
confidence: 77%
“…23) However, an in vitro study showed that bladder cancer cell lines expressed strong telomerase activity with long telomeres, which may, however, be an in vitro artifact. 24) In addition, prompt telomerase activation was observed in a chemical carcinogenesis model of the rat, 25) suggesting that telomerase might be activated at a phase earlier than that of telomere shortening. In view of our findings in this study, telomerase activation might be a primary event during BBN bladder carcinogenesis in the rat, and might lead to malignant conversion without frequent genetic alteration.…”
Section: Discussionmentioning
confidence: 99%
“…Contribution of telomere dysfunction to regional amplification and deletion in cancer genomes was also observed in various mammary cancer systems (O'Hagan et al, 2002). Previous studies have shown that telomerase is expressed in DU145, PC3 and LNCaP (Sommerfeld et al, 1996;Kageyama et al, 1997). However, it has been suggested that despite telomerase expression, telomere-induced anaphase bridges can still occur at a low frequency indicating an ongoing instability process (Stewenius et al, 2005).…”
Section: Bfb-dependent Telomeric Alterationsmentioning
confidence: 96%
“…Studies to date have associated the BFB cycle with telomere shortening observed in HPIN and early invasive foci of carcinoma, contributing to genomic instability and presumably a crisis-like process. However, ongoing BFB in CaP cell lines, known to express telomerase (Sommerfeld et al, 1996;Kageyama et al, 1997) suggests continuation of this CIN mechanism after immortalization. Ongoing but low-level instability via BFB could enable the tumor population to adapt better to changes in the microenvironment and account for some of the tumor heterogeneity seen at later stages of CaP progression.…”
Section: Interpretation Of Chromosomal Instability Findingsmentioning
confidence: 99%